Urban Transformation and Associated Emerging Urban Forms: An Examination of Physical Density from Planning Interventions Perspective - Samuel Zelelew; Zegeye Mamo (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Rapid urbanization frequently results in unanticipated morphological traits that could have multifaceted consequences, especially in the urban physical transformation of cities in developing countries. This study aimed to examine these spatial transformation events and identify the related emergent urban forms in the morphogenesis of Dire Dawa, Ethiopia from the perspective of plan-led and spontaneous developments. The researchers conducted a thorough on-site investigation to gather the necessary physical information and supplemented it with a desk review and focus group discussion. We utilized the Spacematrix software to examine the data and pinpoint the evolving urban structures from different time periods. Overall, the research demonstrated that point-type low-rise development dominated organically developed sites, whereas plan-driven developments were dominated by block-type low-rise and block-type midrise forms. Furthermore, except for outlying areas, there has been a rising trend in the floor space index and spatial coverage patterns over the course of the city’s morphological eras. This may indicate a growing concern for space efficiency and sustainable development. The density of the street network in organically developed portions, on the other hand, was greater than that in formally planned areas. This shows the relevance of considering the concept behind organic development in planning and designing interventions besides the formal western planning philosophy.